2021
DOI: 10.1002/hbm.25371
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of approach‐avoidance conflict decision‐making during functional magnetic resonance imaging in healthy adults

Abstract: Neural and behavioral mechanisms during approach-avoidance conflict decisionmaking are relevant across various psychiatric disorders, particularly anxiety disorders.Studies using approach-avoidance conflict paradigms in healthy adults have identified preliminary neural mechanisms, but findings must be replicated and demonstrated as reliable before further application. This study sought to replicate previous findings and examine test-retest reliability of behavioral (approach behavior, reaction time) and neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…Our AAC task paradigm 19,20 has good test-retest reliability for behavioural responses 36 and fMRI-measured neural activation, 37 supporting its utility for studying individual differences. This task allows for the separate manipulation of decision-making (varying conflict level), affective outcomes (using negative or positive stimuli) and reward feedback (varying reward values).…”
Section: E312mentioning
confidence: 69%
See 3 more Smart Citations
“…Our AAC task paradigm 19,20 has good test-retest reliability for behavioural responses 36 and fMRI-measured neural activation, 37 supporting its utility for studying individual differences. This task allows for the separate manipulation of decision-making (varying conflict level), affective outcomes (using negative or positive stimuli) and reward feedback (varying reward values).…”
Section: E312mentioning
confidence: 69%
“…This task allows for the separate manipulation of decision-making (varying conflict level), affective outcomes (using negative or positive stimuli) and reward feedback (varying reward values). In 2 previous fMRI studies with samples of 15 and 30 healthy adults, 20,37 participants showed distinct regional activations across the following dimensions: for decision-making, greater conflict trials elicited less activity in the amygdala and more in the dorsal anterior cingulate cortex (dACC), dorsal and ventral striatum, and right dorsolateral prefrontal cortex (dlPFC); for affective outcomes, the amygdala, dACC, dorsal and ventral striatum, and anterior insula were more activated by negatively valenced stimuli than by positively valenced stimuli; and for reward feedback, the dorsal and ventral striatum was significantly activated relative to baseline, but its activity did not differ by reward value. However, the neural activations elicited during this task have been examined only in healthy adult samples.…”
Section: E312mentioning
confidence: 99%
See 2 more Smart Citations
“…This goal would require reliable and valid measurement of avoidance behavior at the level of an individual, with known population norms and/or clinical cut points. While some studies have begun to examine construct validity [34,51], psychometric properties of avoidance paradigms have largely not been established (for a notable exception, see [101]). Psychometrically sound tasks will be essential for translation from research to clinical application [102], with test-retest reliability of particular importance for paradigms assessing constructs that should be stable over time, such as trait avoidance tendency.…”
Section: Improving Diagnosis and Treatmentmentioning
confidence: 99%